Coprecipitation of Oxalates: An Easy and Reproducible Wet‐Chemistry Synthesis Route for Transition‐Metal Ferrites. Issue 5 (20th December 2013) - Diodati, Stefano; Nodari, Luca; Natile, Marta Maria; Caneschi, Andrea; de Julián Fernández, César; Hoffmann, Claudia; Kaskel, Stefan; Lieb, Alexandra; Di Noto, Vito; Mascotto, Simone; Saini, Roberta; Gross, Silvia
Abstract: In this work, an easy, quick and reproducible wet‐synthesis coprecipitation route starting from oxalate precursors was optimised to synthesise cobalt, nickel, zinc and magnesium spinel ferrites CoFe2 O4, NiFe2 O4, ZnFe2 O4 and MgFe2 O4, as well as the manganese perovskite ferrite MnFeO3 . Crystalline purity and crystallite sizes ranging from 30 to 190 nm were investigated by means of powder X‐ray diffraction, and uniform morphology of the particles was shown through transmission electron microscopy. The chosen synthetic route afforded an excellent stoichiometric control over the products, as confirmed by combined X‐ray photoelectron spectroscopy and inductively coupled plasma atomic emission spectroscopy analyses. The site geometry, degree of inversion in the spinels and chemical environments in the ferrites were explored by Mössbauer spectroscopy. The thermal evolution of the compounds during calcination and the decomposition pattern of the oxalates were studied through differential scanning calorimetry coupled with thermogravimetric analysis as well as in situ temperature‐programmed X‐ray diffraction. Magnetic properties of these oxides, as well as the transition of the perovskite from paramagnetic to ferrimagnetic behaviour at low temperatures, were investigated by superconducting quantum interferometer magnetometry. Abstract : Cobalt, nickel, zinc and magnesium spinel ferrites CoFe2 O4, NiFe2 O4, ZnFe2 O4 and MgFe2 O4, as well as the manganese perovskite MnFeO3, with high purities, crystallinity and yields have been synthesised through the coprecipitation of oxalates. The obtained oxides have been thoroughly characterised from a structural, compositional, morphological and functional point of view.